Histological evaluation of bovine tunica albuginea as biomaterial conserved in 98% glycerin and in 0.625% glutaraldehyde - Oliveira, Leticia Leal; Barata, Julielton de Souza; da Silva, Alexandre Vinícius Pereira; de Carvalho, Eulógio Carlos Queiróz; Nunes, Louisiane de Carvalho; Abílio, Edmundo Jorge (Brazilian Journal of Veterinary Medicine, 2015)
ABSTRACT. Oliveira L.L., Barata J.S., Silva A.V.P., Caravalho E.C.Q., Nunes L.C. & Abílio E.J. [Histological evaluation of bovine tunica albuginea as biomaterial conserved in 98% glycerin and in 0.625% glutaraldehyde.] Avaliação histológica da túnica albugínea bovina como biomaterial conservada em glicerina a 98% e em glutaraldeído a 0,625%. Revista Brasileira de Medicina Veterinária, 37(4):309-315, 2015. Departamento de Medicina Veterinária, Universidade Federal do Espírito Santo, Alto Universitário s/n, Guararema, Alegre, ES 29500-000, Brasil. E-mail: leticialealolive@hotmail.com Biomaterials have long been studied in reconstructive surgery, both natural and synthetic origin. It can be used as support to host tissue cells development and an efficient bed of stem cells for tissue engineering and regeneration of tissues and organs. The aim of this study was to evaluate the tunica albuginea as biomaterial preserved in glycerin 98% and glutaraldehyde 0.625% and analyze its integrity for use in grafting therapy by microscopic examinations. Tunica albuginea were obtained from healthy adults crossbred cattle from slaughterhouse, tunicas albugineas were preserved in 98% glycerin and 0.625% glutaraldehyde for a period of 30 days at least. Tunica albuginea was fixed in 10% formalin, histologically processed and stained by hematoxylin-eosin, Masson’s trichrome and red picrosisrius polarization. Macroscopically there was a difference in the texture and color of tunica albuginea and in glutaraldehyde group were more firm and thick. Microscopic evaluation revealed that both the glycerin and the glutaraldehyde can be used as conservation medium in function of preserving the basic architecture tissue of the tunica albuginea, however, the glycerin was more efficient preservation of cellular structures. Histochemical techniques have highlighted the collagen and elastic fibers present in tunicas albugineas and highlight the predominance of type I collagen refringence revealing more pronounced in samples preserved in glycerin.